Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
By wrapping PE material on the surface of aramid fiber and preparing lithium-ion battery separators using electrostatic coaxial spinning technology, the problem of insufficient thermal stability of existing separators at high temperatures is solved, and higher film rupture temperature and thermal stability are achieved , improving the safety and energy density of the battery cell.
Patent Information
- Application Number
- CN202411309499.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-07
AI Technical Summary
The existing lithium-ion battery separators lack thermal stability at high temperatures, which can easily lead to short-circuit contact with positive and negative electrodes and thermal runaway.
Aramid fiber is used as a heat-resistant substrate and a layer of PE material is wrapped on its surface. The diaphragm is prepared by electrostatic coaxial spinning technology to improve its rupture temperature and thermal stability.
The rupture temperature and thermal stability of the diaphragm are significantly improved, the thickness of the diaphragm is reduced, and the safety and energy density of the battery cell are enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used due to their high energy density, long cycle life, and environmental protection. With the improvement of the quality of life, people have more and more stringent requirements on battery life and safety.
[0003] As one of the four main materials of lithium-ion batteries, the diaphragm plays the role of isolating the positive and negative electrodes from contact and conducting lithium ions. However, as the entire industry pursues energy density and single battery capacity, the battery cells of the entire industry have transitioned from low capacity and low energy density to high capacity and high energy density, and the chemical system has changed from low gram capacity graphite to high gram capacity silicon and graphite, thereby achieving high energy density. Although this chemical system has great advantages in performance, safety is still a pain point for the entire industry. For example, the hot box has been difficult to improve thoroughly.
[0004] As a polymer material with high heat resistance, aramid has attracted the attention of many R&D personnel in the industry. The high-porosity diaphragm made of it as the main material maintains extremely strong thermal stability during high-temperature baking, and the thermal shrinkage at the same temperature is much smaller than that of the high-porosity diaphragm made of polyolefins such as HDPE and PP. It is more stable than HDPE and PP diaphragms at high temperatures and is not prone to short-circuiting the positive and negative electrodes. However, there are very few cases of its industrialization in the lithium-ion battery industry; at high temperatures, the chemical activity inside the lithium-ion battery is high, causing the temperature to rise sharply. Excessive temperature causes the internal weak point diaphragm to melt first, causing the positive and negative electrodes to short-circuit, and thermal runaway. When the conventional HDPE and PP diaphragms reach the TG temperature, they are closed first compared to the aramid diaphragms, shutting down the electrochemical reaction and delaying thermal runaway.
[0005] In view of the above-mentioned defects existing in the current lithium-ion battery separators, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention
[0006] The purpose of the present invention is to provide a lithium ion battery separator to solve the problems of low membrane rupture temperature and low thermal stability based on polyolefin.
[0007] A lithium-ion battery separator comprises aramid fiber and PE material coated on the surface of the aramid fiber. The membrane breaking temperature of the lithium-ion battery separator is a, and a satisfies the relationship: a≥300°C.
[0008] Preferably, the molecular weight of the aramid fiber is 20,000 to 30,000; and the molecular weight of the PE material is 40,000 to 300,000.
[0009] Preferably, the diameter of the aramid fiber is 5 to 100 μm.
[0010] Preferably, the thickness of the lithium-ion battery separator is 7 to 10 μm.
[0011] Preferably, the longitudinal shrinkage rate of the lithium-ion battery separator at 130°C is b, and b satisfies the relationship: b≤0.5%; the transverse shrinkage rate at 130°C is c, and c satisfies the relationship: c≤0.43%.
[0012] Preferably, the closed-cell temperature of the lithium-ion battery separator is d, and d satisfies the relationship: d≥112°C.
[0013] In a second aspect of the present invention, a method for preparing a lithium ion battery separator is also provided, comprising the following steps:
[0014] Step 1: dissolving meta-aramid in NMP to obtain solution A, and dissolving PE in p-xylene to obtain solution B; injecting solution A and solution B into an electrostatic coaxial spinning machine respectively, wherein solution A flows out from the middle of the coaxial needle, and solution B flows out from the outer circle of the coaxial needle;
[0015] Step 2: Under the action of an electrostatic field, the solution A and the solution B are continuously spun into a diaphragm, and the solvent is removed to obtain a lithium-ion battery diaphragm.
[0016] Preferably, in the step 1, the mass ratio of the meta-aramid to the NMP is (10-20): (80-90); the mass ratio of the PE to the p-xylene is (1-10): (90-99).
[0017] Preferably, in step 1, the mass ratio of solution A to solution B is (25-35):(65-75).
[0018] A lithium ion battery comprises the lithium ion battery separator.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention solves the problem of low membrane rupture temperature based on polyolefin by wrapping a layer of PE material on the surface of aramid fiber and using aramid fiber as a heat-resistant substrate; improves the thermal stability of the diaphragm and further reduces the thickness of the diaphragm. DETAILED DESCRIPTION
[0020] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] According to the first aspect of the present invention, a lithium-ion battery separator is provided, comprising aramid fiber and PE material coated on the surface of the aramid fiber, wherein the membrane breaking temperature of the lithium-ion battery separator is a, and a satisfies the relationship: a ≥ 300° C. The structural advantage of the aramid fiber being inside and the PE material coated on the surface is that when the coated PE layer reaches its melting point, it melts and flows into the fiber pores due to capillary action, thereby preventing lithium ion transmission, thereby closing the electrochemical reaction and improving the safety of the battery cell.
[0022] In one embodiment of the present invention, the molecular weight of the aramid fiber is 20,000 to 30,000; the aramid fiber in this molecular weight range has excellent mechanical properties and heat resistance, which is conducive to the preparation of lithium ion diaphragms with excellent performance; the molecular weight of the PE material is 40,000 to 300,000; the PE material in this molecular content range is the most widely used at present and is suitable for lithium ion batteries.
[0023] In one embodiment of the present invention, the diameter of the aramid fiber is 5 to 100 μm; the aramid fiber within this diameter range has good mechanical properties and can be well suited for processing to prepare a lithium ion separator with better performance.
[0024] In one embodiment of the present invention, the thickness of the lithium ion battery separator is 7-10 μm. The separator of the present invention has extremely strong thermal stability and does not need to be coated with a ceramic layer, which can further reduce the thickness of the separator and improve the energy density of the battery cell.
[0025] In one embodiment of the present invention, the longitudinal shrinkage rate of the lithium-ion battery separator at 130°C is b, and b satisfies the relationship: b≤0.5%; the transverse shrinkage rate at 130°C is c, and c satisfies the relationship: c≤0.43%. The lithium-ion battery separator of the present invention has good heat resistance and a small shrinkage rate at high temperature, which can solve the safety problem of the battery core.
[0026] In one embodiment of the present invention, the closed-cell temperature of the lithium-ion battery separator is d, and d satisfies the relationship: d≥112°C.
[0027] According to a second aspect of the present invention, there is provided a method for preparing a lithium ion battery separator, comprising the following steps:
[0028] Step 1: dissolving meta-aramid in NMP to obtain solution A, and dissolving PE in p-xylene to obtain solution B; injecting solution A and solution B into an electrostatic coaxial spinning machine respectively, wherein solution A flows out from the middle of the coaxial needle, and solution B flows out from the outer circle of the coaxial needle;
[0029] Step 2: Under the action of the electrostatic field, solution A and solution B are continuously spun into a diaphragm, and the solvent is removed to obtain a lithium-ion battery diaphragm.
[0030] In one embodiment of the present invention, in step 1, the mass ratio of meta-aramid to the NMP is (10-20): (80-90); the mass ratio of PE to the p-xylene is (1-10): (90-99).
[0031] In one embodiment of the present invention, in step 1, the mass ratio of solution A to solution B is (25-35):(65-75).
[0032] According to a third aspect of the present invention, there is also provided a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, a battery casing and a lithium ion battery separator thereon.
[0033] The present invention will be further described below by means of specific examples.
[0034] Example 1
[0035] Preparation of lithium-ion battery separator:
[0036] Step 1: dissolving meta-aramid in NMP to obtain solution A, dissolving PE in p-xylene to obtain solution B; injecting solution A and solution B into an electrostatic coaxial spinning machine respectively, wherein the mass ratio of solution A to solution B is 30:60, solution A flows out from the middle of the coaxial needle, and solution B flows out from the outer ring of the coaxial needle, the mass ratio of meta-aramid to NMP is 15:85; the mass ratio of PE to p-xylene is 5:95;
[0037] Step 2: Under the action of an electrostatic field, solution A and solution B are continuously spun into a diaphragm, and the solvent is removed to obtain a lithium-ion battery diaphragm with a thickness of 10 μm.
[0038] Preparation of lithium-ion batteries:
[0039] The negative electrode sheet, the positive electrode sheet and the above-mentioned separator are interlaced and wound and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is lithium iron phosphate; the electrolyte salt of the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:2:1, and the electrolyte concentration is 1 mol / L.
[0040] Table 1 shows the parameters of Examples 1 to 10, and the rest are the same as Example 1 and will not be described again.
[0041] Table 1
[0042] Aramid fiber molecular weight PE material molecular weight Aramid fiber diameter / (μm) Diaphragm thickness / (μm) Example 1 15000 50000 50 10 Example 2 15000 50000 50 7 Example 3 15000 50000 50 9 Example 4 20000 50000 50 10 Example 5 30000 50000 50 10 Example 6 15000 40000 50 10 Example 7 15000 300000 50 10 Example 8 15000 200000 50 10 Example 9 15000 50000 5 10 Example 10 15000 50000 100 10
[0043] Comparative Example 1
[0044] Preparation of diaphragm:
[0045] The alumina ceramic coating is gravure coated on one surface of a PE base film with a thickness of 10 microns, wherein the thickness of the alumina ceramic coating is 2 microns and the total thickness of the diaphragm is 12 microns.
[0046] Preparation of lithium-ion batteries:
[0047] The negative electrode sheet, the positive electrode sheet and the above-mentioned separator are interlaced and wound and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is lithium iron phosphate; the electrolyte salt of the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:2:1, and the electrolyte concentration is 1 mol / L.
[0048] Comparative Example 2
[0049] Preparation of diaphragm:
[0050] The coating of aramid mixed inorganic and organic polymers is coated on at least one surface of the PE base film, and then the coated film is rewound, slit, and rolled to obtain an aramid diaphragm with a total thickness of 15 μm.
[0051] Preparation of lithium-ion batteries:
[0052] The negative electrode sheet, the positive electrode sheet and the above-mentioned separator are interlaced and wound and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is lithium iron phosphate; the electrolyte salt of the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:2:1, and the electrolyte concentration is 1 mol / L.
[0053] Performance Testing:
[0054] The diaphragms of Examples 1 to 10 and Comparative Examples 1 to 2 were subjected to closed-cell rupture temperature tests, and the test results are shown in Table 2;
[0055] The lithium ion batteries of Examples 1 to 10 and Comparative Examples 1 to 2 were subjected to a hot box test, and the test results are shown in Table 3;
[0056] Table 2
[0057]
[0058] Table 3
[0059]
[0060]
[0061] As shown in Table 2, it can be seen from the data comparison of Examples 1 to 10 and Comparative Examples 1 to 2 that the lithium ion battery separator of the present invention solves the problem of low membrane rupture temperature based on polyolefin by wrapping a layer of PE material on the surface of aramid fiber and using aramid fiber as a heat-resistant substrate;
[0062] Specifically, the film rupture temperature data of Examples 1 to 10 are much higher than those of Comparative Examples 1 to 2, which solves the problem of low film rupture temperature based on polyolefin; the thermal shrinkage data of Examples 1 to 10 are much better than those of Comparative Examples 1 to 2, indicating that the diaphragm prepared by the scheme of the present application has better thermal stability than the diaphragm of Comparative Examples 1 to 2.
[0063] As shown in Table 3, by comparing the data of Examples 1 to 10 and Comparative Examples 1 to 2, it can be seen that the hot box test pass rate of Examples 1 to 10 is much higher than that of Comparative Examples 1 to 2, further illustrating that the lithium ion battery separator of the present application has excellent thermal stability.
[0064] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium ion battery separator, characterized in that: It comprises aramid fiber and PE material coated on the surface of the aramid fiber, and the membrane breaking temperature of the lithium ion battery separator is a, and a satisfies the relationship: a≥300°C.
2. The lithium-ion battery separator according to claim 1, characterized in that The molecular weight of the aramid fiber is 20,000 to 30,000; the molecular weight of the PE material is 40,000 to 300,000.
3. The lithium ion battery separator according to claim 1, characterized in that: The diameter of the aramid fiber is 5 to 100 μm.
4. The lithium-ion battery separator according to claim 1, characterized in that The thickness of the lithium ion battery separator is 7 to 10 μm.
5. The lithium ion battery separator according to claim 1, characterized in that: The longitudinal shrinkage rate of the lithium-ion battery separator at 130° C. is b, and b satisfies the relationship: b≤0.5%; the transverse shrinkage rate at 130° C. is c, and c satisfies the relationship: c≤0.43%.
6. The lithium-ion battery separator according to claim 1, characterized in that: The closed-cell temperature of the lithium-ion battery separator is d, and d satisfies the relationship: d≥112°C.
7. A method for preparing a lithium ion battery separator according to any one of items 1 to 6, characterized in that: The following steps are involved: Step 1: dissolving meta-aramid in NMP to obtain solution A, and dissolving PE in p-xylene to obtain solution B; Injecting the solution A and the solution B into an electrostatic coaxial spinning machine respectively, wherein the solution A flows out from the middle of the coaxial needle and the solution B flows out from the outer circle of the coaxial needle; Step 2: Under the action of an electrostatic field, the solution A and the solution B are continuously spun into a diaphragm, and the solvent is removed to obtain a lithium-ion battery diaphragm.
8. The method for preparing a lithium ion battery separator according to claim 5, characterized in that: In the step 1, the mass ratio of the meta-aramid to the NMP is (10-20): (80-90); the mass ratio of the PE to the p-xylene is (1-10): (90-99).
9. The method for preparing a lithium ion battery separator according to claim 5, characterized in that: In the step 1, the mass ratio of the solution A to the solution B is (25-35):(65-75).
10. A lithium ion battery, characterized in that: The invention comprises the lithium ion battery separator according to any one of claims 1 to 5.
Citation Information
Patent Citations
High-temperature resistant aromatic polysulfonamide base lithium ion battery diaphragm
CN102969471A
Special diaphragm for lithium ion batteries and preparation method of special diaphragm for lithium ion batteries
CN105762318A
Preparation method of battery diaphragm and battery diaphragm
CN114024096A
Isolating membrane and preparation method thereof, secondary battery and electric device
CN115832623A
Thermal response composite diaphragm and preparation method thereof
CN116706427A